Epidemiological and parasitological approaches to human leishmaniasis in the Meknes region, Morocco - Abdelfatah, Benchahid.; Driss, Belghyti.; khadija, El kharrim. (Edelweiss Applied Science and Technology, 2025)
Leishmaniasis is a parasitic disease common to humans and animals, caused by the Leishmania parasite. It represents a major public health problem in Morocco and in many tropical and subtropical areas of the world. These parasitoses are transmitted by infected sandflies and are influenced by environmental, social, and biological factors. The aim of our research is to assess the epidemiological situation of leishmaniasis and to analyze the spatio-temporal distribution of new cases of leishmaniasis in the Meknes region. In light of this work, we carried out a retrospective study after Covid-19, collating all cases of cutaneous and visceral leishmaniasis recorded in the Meknes region. These epidemiological data were collected from special registers at the health establishment network service. In total, we collected thirty-one (31) registered infected cases. These epidemiological data show that there is a coexistence of the two forms of leishmaniasis: cutaneous (83.87%) and visceral (16.13%), with a predominance of rural areas. The sex ratio was 0.82, and the average annual incidence was 9 cases per year. These parasitoses affect all age groups and are not influenced by sex. Moreover, visceral leishmaniasis only infects cases under nine years of age (< 9). To combat these leishmaniases, especially in rural areas, it is crucial to adopt different epidemiological, parasitological, and sociological approaches.